A triple helix case: Innovative and sustainable international summer school in China - Jabbar Al-Obaidi; Chien Wen Yu (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This article explored the International Summer School model in China. Its goals are to evaluate the curriculum and its features and to analyze how the Triple Helix Theory of Innovation is used. In the summer of 2019, Uni vPlus-BSU Shanghai Program and UnivPlus-FSU Beijing Program students were surveyed. Methodology: One hundred fifteen students from BSU (Shanghai) and FSU (Beijing) were given a survey consisting of 13 questions. The authors gathered information on the summer programmes’ effectiveness by surveying both students and teachers. Volunteers from each campus filled out the survey, resulting in a skewed sample. Findings: UnivPlus is one of the leading organisations providing international summer schools in China for Chinese international students attending universities in the United States and Canada and using their summer breaks in China to study and earn transfer credits. Innovation through collaboration between the academic world and private and public sectors is called the